Ighlāq al-Masājid Man’an lī intishār Fayrūs Corona Dirāsah Taḥlīlīyah fī Ḍaw’ Maqāṣid al-Sharī`ah - Habeebullah Zakariyah; Turki Obaid Al-Marri; Bouhedda Ghalia (Faculty of Sharia IAIN Madura collaboration with The Islamic Law Researcher Association (APHI), 2020)
Many Muslim countries prohibit mosques opening because social gathering is regarded as a high probable factor for Corona Virus infection. This paper discusses different opinions of some contemporary scholars on this issue from the Maqāṣidī perspective. It adopts an analytical method to explain the opinions. Findings show that contemporary scholars are of two group: The first group permits the mosques’ closure for realizing the divine objective concerning to life protection out of danger. The second thinks that the mosques’s closure amounts to suspension of congregational prayer as one of Islamic essential exterior rites. The findings illustrate that the life protection constitutes a necessary benefit because putting life in danger is a very serious harm. The life protection is more important than congregational prayer’s objective which complements the necessary objective of religious protection. Moreover, it shares the spirit with the principle saying that any means to achieving what is compulsory also becomes compulsory accordingly. Above all, prohibition of congregational prayer is just a momentary legal permit due to a necessity on its merit the research recommends that religious institution should make people aware to take all measures in stopping the spread of Covid-19 pandemic.أمرت كثير من الدول الإسلامية بإغلاق المساجد باعتبار أن التجمع فيها يمثل سببا محتملا لوقوع العدوى. تهدف الورقة إلى مناقشة آراء العلماء المعاصرين وأدلتهم تجاه هذه القضية وتحليلها في ضوء مقاصد الشريعة. استخدمت الورقة المنهج التحليلي في بيان آراء العلماء المعاصرين والموازنة بين المقاصد. أظهرت نتائج الورقة أن العلماء المعاصرين منقسمون إلى قسمين: فطائفة ترى جواز إغلاق المساجد؛ لأنه يحقق مقصود الشارع في حفظ النفوس من الهلاك، وطائفة أخرى ترى أن هذا الإغلاق تعطيل لشعيرة صلاة الجماعة التي هي شعيرة من شعائر الإسلام الظاهرة. كما أوضحت النتائج أن مصلحة حفظ النفس تمثل مقصدا ضروريا وفوات الأنفس ضرر لا يمكن جبره؛ وهو أقوى في مرتبته من مقصد الصلاة جماعة من حيث إنه في مرتبته مكمل لضروري حفظ الدين. وأن تعطيل الجماعة في الصلاة يمثل رخصة مؤقتة ولضرورة تقدر بقدرها، ولأنها شعار المسلمين، فهو مصلحة مكملة لضروري حفظ الدين، وعليه فالتعارض واقع بين مقصدين متفاوتين في المرتبة، وعليه، فالقول بفتوى غلق المساجد أرجح باعتبار تحقيق المناط؛ ولأنه يحقق مقاصد الشريعة العليا المتمثلة في حفظ الأنفس المعصومة من الهلاك في الجملة. وتوصي الورقة المؤسسات الدينية بالقيام بتوعية الناس بأهمية اتخاذ التدابير الاحترازية لمنع تفشي هذه الجائحة العالمية